Evaluasi Penerapan E-Government Di Pemerintah Kabupaten Sumbawa Besar Menggunakan Kerangka Kerja Sistem Pemerintahan Berbasis Elektronik (SPBE) - Hemy Dwi Pratiwi; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The Sumbawa Regency Government, as part of the Indonesian government agency, has begun to carry out improvements to the performance of its government in line with the government's bureaucratic reform program, which is to reorganize, change, improve and perfect the bureaucracy to become more efficient, effective and productive. However, on the results of the Government Institution Performance Accountability Assessment System (SAKIP), for 2 years (2017-2018), Sumbawa Regency won the